Transfer pricing reforms in the context of BEPS: challenges remain - S. S. Pyroha (Law and Safety, 2024)
The presence of affiliated entities in different countries and the independence of tax systems make it easy to shift profits from jurisdictions with high corporate tax rates to jurisdictions with low rates. Transfer prices and the arm's length principle are used to prevent profit shifting. The article identifies the peculiarities of transfer pricing reform in the context of the BEPS plan, analyses changes to Ukrainian legislation and opportunities for its improvement.